2008
DOI: 10.1111/j.1365-2567.2008.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory glycan LNFPIII initiates alternative activation of murine macrophages in vivo

Abstract: Summary The early pathogen–macrophage interactions that help drive macrophage maturation towards classically or alternatively activated are largely unknown. To examine this question we utilized the immunomodulatory glycan Lacto‐N‐fucopentaose III (LNFPIII), which contains the Lewis X (LeX) trisaccharide, to activate murine peritoneal macrophages in vivo. Because LNFPIII is known to induce anti‐inflammatory responses, we asked if LNFPIII stimulation of macrophages in vivo initiates alternative activation events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 67 publications
1
77
0
Order By: Relevance
“…Previous studies reported that the expression of survivin was significantly increased in patients with a higher tumor grade of urinary tract malignancies [27][28][29][30][31][32]. Swana et al shown that bladder cancer patients with higher survivin expression have a shorter time to recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the expression of survivin was significantly increased in patients with a higher tumor grade of urinary tract malignancies [27][28][29][30][31][32]. Swana et al shown that bladder cancer patients with higher survivin expression have a shorter time to recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…The Lewis x trisaccharide is abundantly expressed on schistosome egg antigens and is the terminal trisaccharide of the LNFPIII pentasaccharide that we have used to study pathogen/self glycan activation of innate immune responses (10,26). LNFPIII neoglycoconjugates (LNFPIII-NGC) comprised of multiple (7 to 10) LNFPIII moieties conjugated via linker-spacer technology to carrier molecules have been employed to determine how LNFPIII/ Lewis x activates and induces alternative activation of APCs and drives anti-inflammatory responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived dendritic cells (BMDCs) were obtained by flushing bone marrow cells in RPMI 1640 and culturing the cells with 20 ng/ml of granulocyte-macrophage colony-stimulating factor (GM-CSF; PeproTech, Rocky Hill, NJ) essentially as described previously (10). On days 3 and 5, fresh medium containing GM-CSF was added to the cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations